Key Kinematic Components for Optimal Basketball Free Throw Shooting Performance - Dimitrije Cabarkapa; Andrew C. Fry; Kevin M. Carlson; John P. Poggio; Michael A. Deane (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
The purpose of this study was to determine the difference in five kinematic variables (internal knee and elbow angles, elbow height, forearm angle from vertical, and shoulder flexion angle at ball release) between proficient and non-proficient free throw shooters and which variables had the greatest contributions to a successful free throw shooting outcome. Seventeen male basketball players shoot three sets of 10 free throws with a two-minute break between each set. A three-dimensional motion tracking system composed of 17 sensors sampling at 60 Hz was used for data collection. Proficient free throw shooters had greater knee and elbow flexion, lower elbow height, and a smaller forearm angle compared to non-proficient shooters. These results explained 89.5% of the total variance. While maintaining the optimal range of these kinematic variables allows each subject to reach an appropriate level of free throw shooting performance, the key variable capable of distinguishing between made and missed shots within the proficient group of shooters was the forearm angle. Positioning the forearm parallel, or close to parallel, with an imaginary vertical line during the preparatory phase of the shooting motion accounted for 23.9% of the total variance and was associated with a greater number of made shots.